A comparison between the recovery responses following an eccentrically loaded bench press protocol vs. regular loading in highly trained men - Bartolomei, S.; Totti, V.; Nigro, F.; Ciacci, S.; Semprini, G.; Di Michele, R.; Cortesi, M.; Hoffman, J. R. (Journal of Human Kinetics, 2019)
The purpose of this study was to compare the physiological responses of a single bout of an eccentric accentuated bench press protocol (120% of 1RM in the eccentric phase/80% in the concentric phase; [120/80]) versus a regular high-intensity exercise protocol (80%/80%; [80/80]) in resistance-trained men. Eleven men (age = 25.6 ± 3.9 y; body mass = 84.6 ± 11.2 kg; body height = 176.4 ± 3.9 cm) with 6.3 ± 3.4 y of resistance training experience performed each protocol in counterbalanced, randomized order. Isometric, isokinetic and ballistic tests were performed at the bench press (IBPF, ISOK and BTP, respectively) at baseline (BL), 15-min (15P), 24-h (24P), and 48-h (48P) post-exercise for each testing session. In addition, muscle thickness of the pectoralis major (PecMT) was measured at the same timepoints via ultrasound. Significantly greater reductions in BTP (p < 0.001), peak force during both ISOK (p = 0.005) and IBPF (p = 0.006) at 15P were detected in 120/80 compared to 80/80. BTP was still significantly (p = 0.009) impaired at 48P following the 120/80 protocol, while no differences were noted following 80/80. PecMt was significantly elevated following both 120/80 and 80/80 (p < 0.05) at 15P, but significant differences between the trials were present at 15P and 24P (p = 0.005 and p = 0.008, respectively). Results indicated that heavy eccentric loading during the bench press exercise caused greater performance deficits than a bout of traditionally loaded high intensity resistance exercise. Power performance appears to be more influenced by the 120/80 protocol than isometric peak force. Eccentrically loaded exercise sessions should be separated by at least 48 hours to obtain a complete recovery of the initial muscle morphology and performance.